Indoor air pollution and environmental tobacco smoke exposure in a South African birth cohort study - Vanker, Aneesa (Division of Pulmonology, 2019)
middleincome countries (LMIC) and a major reason for health care visits and hospitalisation. Environmental exposures to indoor air pollution (IAP) or tobacco smoke are important risk factors for childhood respiratory disease. Despite increased electrification, many communities in LMIC rely on alternate fuel sources for household cooking or heating. The impact of antenatal or postnatal exposures on early childhood respiratory disease has not been comprehensively studied in LMIC especially in Africa. The aim of this work was to investigate the impact of IAP and environmental tobacco smoke (ETS) exposure on child health and early-life respiratory disease in the Drakenstein Child Health Study (DCHS), a South African birth cohort study. The DCHS investigates the epidemiology and impact of early-life exposures on child health including lung disease. The study is set in a peri-urban poor community in the Western Cape, South Africa. Pregnant women were enrolled from two public primary healthcare clinics, Mbekweni (serving a predominantly black African population) and Newman (predominantly mixed-ancestry population) and 1000 mother-infant pairs longitudinally followed from birth through 1 year of life. The thesis chapters are presented as published manuscripts that describe IAP and ETS exposure in the 2 communities in the DCHS cohort from the antenatal period and the impact of these exposure on child health and lung diseases, LRTI and wheezing illness in the first year of life. To measure exposures comprehensively, two home visits, one in the antenatal period (third trimester) and the second postnatally (between 4 and 6 months of the infant’s life), were conducted to assess the home environment and to measure the most common indoor air pollutants and by-products of combustion. Devices placed in participants’ homes measured exposure to particulate matter (PM10), carbon monoxide (CO), nitrogen dioxide (NO2), sulphur dioxide (SO2) and volatile organic compounds (VOC). Maternal and infant urine cotinine measures were used to validate self-reported tobacco smoking and exposure. Study staff trained in recognition of LRTI or wheeze documented all episodes, which were categorised according to WHO case definition criteria. Exposure to IAP was comprehensively assessed in over 800 homes antenatally and postnatally providing important South African data on IAP and potential sources of exposure. Tobacco smoke exposure was assessed longitdunially by maternal self-report using validated scales and by measurement of urine cotinine in mothers and infants. Tobacco smoke exposure was found to be highly prevalent with a smoking prevalence of >50% in mixedancestry mothers. Alarmingly, 18% of infants were born with urine cotinine levels in keeping with active smoking, while a further 30% had levels indicating passive smoke exposure. Key findings were despite 92% of homes reporting access to electricity, there was still a reliance on cheaper alternate fuels. Tobacco smoking prevalence amongst pregnant women was high (32%), as was household exposure to tobacco smoke (44%). ETS exposure was associated with low birth weight and antenatal IAP or ETS exposure was significantly associated with increased LRTI. ETS exposure was also associated with wheezing illnesses. A novel finding was that antenatal exposure to toluene, a volatile organic compound, was associated with severe LRTI and hospitalisation. The timing of environmental exposures on the subsequent development of LRTI in infancy has not been well described. An important finding was that antenatal exposures were the main risk factors associated with LRTI, with maternal smoking in pregnancy or PM10 exposure most strongly associated with LRTI. Wheezing illness was associated with both antenatal and postnatal maternal smoking and antenatal maternal smoke exposure and postnatal household member smoking. Both IAP and ETS exposure impacted on both maternal and infant nasopharyngeal bacterial carriage which may be a precursor to the development of LRTI. Environmental exposures therefore had a substantial impact on child health and on LRTI and wheezing illness. The effect on LRTI of antenatal compared with postnatal exposure suggests an in utero developmental lung effect. This study highlights antenatal and early life as a critical period for lung development. Urgent and effective smoking cessation programmes targeting women of child bearing age as well as public health interventions to reduce IAP are required. Woman of childbearing age, pregnant women and children in poor communities represent vulnerable populations at risk for long-term health effects of these exposures.